동북아 국제질서의 구조적 특성과 한반도 문제 해결방향 - 길병옥; Byung Ok Kil; 김학성; Hak Sung Kim (한국과 국제정치, 2004)
Possibilities of making self-fulfilling roles for South Korea to resolve problems on the Korean peninsula are open since structural obstacles overcoming national separation become obsolete after the demise of the Cold War. Despite the fact that any optimism for the future is not allowed in the midst of political turmoils and changes in Northeast Asia, there are concrete ways of changing the future through the internal expansion of abilities and external utilization of security environment for the national integration of two Koreas. Two perspectives of ‘peninsularization of the Korean problem’ and ‘internationalization of the Korean problem’ are in conflict. But realistically, South Korea needs to consider both national and international aspects to resolve the problem. In other words, to have positive roles of domestic and international actors in the process of national unification, South Korea must seek incremental changes of the Northeast Asian security structure from bilateralism to multilateralism like the Northeast Asian multilateral security system. KCI Citation Count: 4